Jews of the Sahara - Nagel, Ronald L. (Einstein Journal of Biology and Medicine, 2004)
Many years ago, my French colleague and collaborator, Dominique Labie, had arranged a scientific trip to Algeria to study hemoglobinopathies in Algiers (Mears et al., 1981; Pagnier et al., 1984). After several days of intense work, Cherif Beldjord, the younger of our hosts, proposed that we take the weekend off and go to Ghardaia. To entice us, he said, “It will be a fun trip to the Sahara desert, and you cannot imagine how beautiful the place is.” Dominique and I rapidly signed up for this great opportunity. Finally, I would see the Sahara desert, the magical and mysterious Sahara desert.
Keywords: Judaïsme -- Mzab